Correlação da sorologia do pré-natal com análise parasitológica de placentas em gravidez de risco para TORCHS com ênfase em toxoplasmose - Lourenço, Ana Flávia Eugênio (2009)
Infections from the group TORCHS in a pregnant woman include diseases transmitted by protozoa (toxoplasmosis), virus (rubella, cytomegalovirus and common herpes) and bacteria (syphilis). These can be acquired congenitally causing risks to health of the conceptus and it has a great impact on our environment, for that, are so embedded in routine examinations for pre-natal care of pregnant women. Knowing that the placenta acts as a barrier that hinds and often prevents the passage of microorganisms, there was an evaluation in this study to compare the results of immunological tests, parasitological and anatomapatalogical of seropositive women classified at risk for syndrome of TORCHS. They studied 32 placental samples from patients that during the pre-natal showed positive serology for one of the infections belonging to syndrome of TORCHS. These patients were screened by the maternity of the Hospital das Clinicas, by the department of gynecology and obstetrics. In this process of study, only pregnant women that after all the information given, signed an informed consent and answered a questionnaire, so that epidemiological data could be obtained participated. The samples were sent to the pathology department of the same hospital for the biopsy. And also, a small part of the placental samples were sent to the Institute of Tropical Pathology and Public Health in the field of parasitology UFG to perform parasitological examination. The results of the serological tests were provided by the laboratory of the Hospital das Clinicas or by the APAE (Association of Parents and Friends of Exceptional. These pregnant women had mean age of 25.5, where 53.1% of them were in their first pregnancy (18.1% had two, three 3.1% and 15.7% four or more pregnancies), the number of abortions earlier in pregnancy was 25%. The ones that had completed High School was 62.5%, 31.25% were doing or had completed Middle School and 6.25% reported not being alphabetized. The ones that reported working with employment were 12.5 and informal employment 12.5%. 75%. stated that they were unemployed. 72% of them live in Goiania and the remainder (28%) in other towns around Goiania, but in the state of Goias. On the serological results, 78.1% (25/32) had positive serology (IgM and IgG) for toxoplasmosis, 9.4% (3/32) for cytomegalovirus, 9.4% (3/32) for syphilis, and 3.1% (1/32) for rubella. Ana Flávia Eugênio Lourenço – Dissertação de Mestrado IPTSP-UFG 2009 1. xvii Among the 25 patients who were positive for toxoplasmosis serology, 92% had the test of avidity of IgG, whereas only 4% had low avidity, 3% indeterminate and 84% high avidity. The anatomopatalogical examination of the 32 placental samples showed that 15.6% (5/32) had some changes related to infection, and that 80% (4/5) of the women had positive serology for toxoplasmosis and 20% (1/5) serology positive for rubella. In relation to placental weight compared to gestational age, 43.7% were small for gestational age, 28.1% were large and the rest did not present macroscopic changes. Women with positive serology for toxoplasmosis, possibly detected T. gondii in 60% of the placenta. Pregnant women who participated in the study had low levels of formal education and the toxoplasmosis infection was more frequently (25/32) agreed with previous studies on the importance of protozaoal in pregnant women in our country. The isolation of T.gondii in placentas through PCR showed that the placental tissue may be utilized and it’s more sensitive than the anatomopatalogical. The anatomopatalogical exam in the placental tisue shows a low sensitivity by the difficulty of detection of microorganisms and viral inclusions, thus reducing the diagnosis of infection. The importance of determining the best methods of diagnosis of toxoplasmosis in pregnant women is due to the use of appropriate therapy in order to reduce the aggression in those occurring in fetal serologic turning.